Proceedings of the 41st Annual Hawaii International Conference on System Sciences (HICSS 2008) 2008
DOI: 10.1109/hicss.2008.141
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Medical Records: A Review Comparing the Challenges in Developed and Developing Countries

Abstract: 1 Studies on the adaptation of Electronic Medical and Personal Health Records in developing countries are scarce. There are sharp differences between barriers to adaptation and implementation in developing countries to that of developed countries. This paper examines the challenges faced by developing countries toward the development, progression and sustainability of Electronic Medical Records. The paper also provides a review of implementation of varying types of electronic medical data management systems in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 26 publications
2
53
0
Order By: Relevance
“…Sood et al [43] conducted a systematic review to compare different facilitators and barriers in developed and developing countries for successful electronic medical record implementation and use and found a major difference in barriers in those two settings. However, with respect to the implementation of mobile health intervetnions, this type of analysis is lacking and this study aims to fill this evidence gap.…”
Section: Discussionmentioning
confidence: 99%
“…Sood et al [43] conducted a systematic review to compare different facilitators and barriers in developed and developing countries for successful electronic medical record implementation and use and found a major difference in barriers in those two settings. However, with respect to the implementation of mobile health intervetnions, this type of analysis is lacking and this study aims to fill this evidence gap.…”
Section: Discussionmentioning
confidence: 99%
“…When integrating IS it is integral to be aware of the cultural aspects involved (Pliskin et al, 1993). Research has shown that cultures differ between developed and developing countries (Sood et al 2008) which must be incorporated within software development projects. Research in other areas has shown that this integrative approach is effective (cf.…”
Section: Figure 3 Integration Requirements For His In Nigeriamentioning
confidence: 99%
“…Research in other areas has shown that this integrative approach is effective (cf. Chrispin & Katzenstein, 2006;Sood et al, 2008;Biswas et al, 2014;Farag, 2015).…”
Section: Figure 3 Integration Requirements For His In Nigeriamentioning
confidence: 99%
“…The implementation and use of EMR systems has been explored in developed countries for more than three decades, but the progress has been slow such that there continues to be limited adoption and use of the systems in healthcare institutions (Boonstra and Broekhuis, 2010;Chaudhry et al, 2006;Sood et al, 2008). This indicates that successful design and implementation of EMR systems continues to be a challenging task (Chaudhry et al, 2006;Fitzpatrick and Ellingsen, 2012;Vikkelsø, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have identified various design and implementation challenges such as poor electricity and ICT infrastructures, lack of back-up systems, limited health care budget, low staffing levels, high risk of theft, lack of local technical expertise to support the systems, and poor systems security leading to viruses (Douglas, 2009, Fraser et al, 2005, Sood et al, 2008. However, studies are lacking that analyse and discuss the EMR design process and the complexities of balancing the work practices and protocols in the context of developing countries (Fitzpatrick and Ellingsen, 2012).…”
Section: Introductionmentioning
confidence: 99%